Construct a switching mode power supply using digital pulse width modulation (PWM) technique / Safri Ibrahim - Ibrahim, Safri (2003)
This report involves the constructing a Switching Mode Power Supply (SMPS) with the output is 5VDC, using Digital Pulse Width Modulation (PWM) technique. The Xilinx Complex Programmable Logic Devices (CPLD) is to generate the control signal for required Pulse Width Modulation (PWM) switching pattern. In the laboratory testing, the circuit designed work successfully for different input supply voltages. So, Digital Pulse Width Modulation (PWM) pattern is good to use for switching mode power supply.